Clinical Scenarios for Which Cervical Mobilization and Manipulation Are Considered by an Expert Panel to Be Appropriate (and Inappropriate) for Patients With Chronic Neck Pain. Issue 4 (April 2020) - Herman, Patricia M.; Vernon, Howard; Hurwitz, Eric L.; Shekelle, Paul G.; Whitley, Margaret D.; Coulter, Ian D.
Abstract : Objectives: Cervical mobilization and manipulation are 2 therapies commonly used for chronic neck pain (CNP). However, safety, especially of cervical manipulation, is controversial. This study identifies the clinical scenarios for which an expert panel rated cervical mobilization and manipulation as appropriate and inappropriate. Methods: An expert panel, following a well-validated modified-Delphi approach, used an evidence synthesis and clinical acumen to develop and then rate the appropriateness of cervical mobilization and manipulation for each of an exhaustive list of clinical scenarios for CNP. Key patient characteristics were identified using decision tree analysis (DTA). Results: Three hundred seventy-two clinical scenarios were defined and rated by an 11-member expert panel as to the appropriateness of cervical mobilization and manipulation. Across clinical scenarios more were rated inappropriate than appropriate for both therapies, and more scenarios were rated inappropriate for manipulation than mobilization. However, the number of patients presenting with each scenario is not yet known. Nevertheless, DTA indicates that all clinical scenarios that included red flags (eg, fever, cancer, inflammatory arthritides, or vasculitides), and some others involving major neurological findings, especially if previous manual therapy was unfavorable, were rated as inappropriate for both cervical mobilization and manipulation. DTA also identified the absence of cervical disk herniation, stenosis, or foraminal osteophytosis on additional testing as the most important patient characteristic in predicting ratings of appropriate. Conclusions: Clinical guidelines for CNP should include information on the clinical scenarios for which cervical mobilization and manipulation were found inappropriate, including those with red flags, and others involving major neurological findings if previous manual therapy was unfavorable. Abstract : Supplemental Digital Content is available in the text.